(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
Tofu waste processing, both solid, liquid and gas, especially liquid waste has not received optimal processing by the community around the manufacture of tofu in general and especially tofu producers. Whereas in liquid and solid tofu waste there is still protein content that can still be utilized. So that tofu waste can be an additional income for tofu producers. In the process of making nata de soya from tofu liquid waste, it is hoped that it will still contain protein and the weight and thickness of the nata, so that the liquid waste can be used as a new product that is useful for consumption by the public. The purpose of this activity is to utilize the liquid waste by-product of the tofu home industry in the Pakunden Village, Blitar City to increase the economic value into nata de soya products and reduce pollution in the area. Nata de soya is expected to be able to improve the economic level of the Pakunden Village community, Blitar City. The community is very enthusiastic in this activity because the materials are cheap and the market demand is quite high. The income in one production process in the process of making nata de soya is Rp. 785,000 so that the production of nata de soya is profitable.